The effect of different media ads on consumer’s purchase intension: a pragmatic exploration on the Bangladeshi fast food industry - Haque, A. K. M. Ahasanul; Sarwar, Abdullah Al-Mamun; Yasmin, Farzana (International Journal of Management and Business Affairs, 2012)
Advertisement plays a significant role in terms of product or service characteristics clarification to the customer. Regardless of the advertisement’s types, a customer by the exposure of ads will go through specific steps of awareness. Realizing the current needs, this study aimed to examine the relationship between three different types of advertisements and their influence on the customer’s attitude towards fast food industry in Bangladesh. Data were collected by using convenient sampling method from Dhaka city in Bangladesh. The result of the research shows that, consumers have found the online advertising more interesting compared to media and print ads and its due to the rapid growth of internet users. Finally, based on the findings, some recommendations are proposed.